Business and Company Legislation 2022/2023 : Legal Practice Course Guides (LPC). - Ellis (Bristol : College of Law Publishing, 2022)
Published annually, Business and Company Legislation details the main regulations governing the operation of companies in England and Wales. It also includes relevant legislation on insolvency, partnerships (including limited liability partnerships) and financial services.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books